Upaya Guru PAI dalam Pembinaan Akhlak Melalui Budaya Religius Bagi ABK Tunarungu - Lailatul Amanah, Isti; Agustiningsih, Suci; Saputra, Ari (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2021)
This study is motivated by a decline in religious values ​​and religious culture that exist in society. Through moral development in schools, it is possible to improve school culture, especially for children who are not yet fully understood, not least for children with special needs who are deaf. Deafness is a condition of a person who has severe to total deafness which makes it difficult for him to communicate with others because he cannot catch the speech of the interlocutor and see only the lips and body movements of the interlocutor. The aims of this study are to: (1) describe moral development through religious culture for children with hearing impairment (2) analyze moral development through religious culture for children with hearing impairment. The method that the author uses in this research is the method of library research or library research, namely studying, reading, and reviewing books and writings related to the discussion. The results showed that: (1) through the exemplary method (al-Uswah al-Hasanah). The PAI teacher is a figure who sets an example for the Deaf ABK. PAI teachers participate in carrying out school religious culture such as 3S activities (Smile, Greetings, Greetings), participate in congregational prayer activities (2) Through the habituation method (at-Ta'widiyyah) PAI teachers familiarize hearing-impaired ABK to implement school religious culture by always embracing and invites the deaf crew to carry out religious culture (3) through the story method (al-Qishshah) with graphic media, other media aids, exemplary stories and historical stories that can motivate the deaf crew members accompanied by illustrations to support the story (4) through the coaching method ( at-Tadrib) The coaching method is a method of moral development by inviting parties to train themselves through certain activities. In this case, the PAI teacher can invite the deaf children to learn to recite the Koran in sign language.